Pollutant removal by Canna Generalis in tropical constructed wetlands for domestic wastewater treatment - H.D. Tran; H.M.T. Vi; H.T.T. Dang; R.M. Narbaitz (Global Journal of Environmental Science and Management)
Constructed wetlands have not been commonly used in Vietnam due to the lack of information in the selection of proper types of constructed wetlands, type of reeds, design parameters and performance efficiency, in tropical climates. This paper focuses on Canna generalis, which is a common reed and easy to grow both in water and wet land conditions. Two kinds of hybrid constructed wetlands were employed, including Facultative pond combined with free water sub-surface constructed wetlands system and horizontal subsurface flow combined with Aerobic pond system. It was found that the ponds played an important role in the hybrid system performance and enhanced the performance of constructed wetlands. The pollutant removal efficiencies of the hybrid systems were all higher than the single constructed wetlands. The BOD5, TSS, NH4-N and PO4-P removal efficiencies averaged 81%, 85%, 93% and 77%, respectively for the hybrid horizontal subsurface flow constructed wetlands system operated at a hydraulic loading rate of 0.075 m/day, while they were 89%, 97%, 97%, and 68%, respectively for the hybrid free water sub-surface constructed wetlands system operated at a hydraulic loading rate of 0.1 m/day. The removal rate constants (kBOD5, kNH4-N, kPO4-P) of the experimental hybrid constructed wetlands were similar to those in previous studies. However, these constants were higher for the hybrid free water subsurface constructed wetlands because of the modified structure flow of the free water subsurface constructed wetlands applied in this study, compared to conventional ones, as well as the additional benefits of the ponds in the hybrid systems.